Evaluasi Standar CDOB 2025 dalam Penyimpanan Sediaan Farmasi di Pedagang Besar Farmasi (PBF) Penta Valent Cabang Semarang dan Surakarta - Relita Saswita Purdianti; Fatiha Khiesa Wardhani; Tifani Agnes Prameswari; Agitya Resti Erwiyani; Renalitha Devri Adriana; Myrna Ayu Nursetya Utami (SEHATI: Jurnal Kesehatan, 2026)
Drug distribution is a vital component in ensuring the availability of quality, safe, and efficacious medicines. Improper storage can decrease drug stability and therapeutic effectiveness. This study aims t evaluate the drug strage system and onditions at PBF Penta Valent Semarang and Surakarta based on the Good Distribution Practice (GDP/CDOB) standards according to BPOM regulation No. 20 of 2025. Methods : This research employed a descriptive qualitive approach through direct observation of storage facilities, environmental control, stock arrangement systems, and special medicine management during September 2025. Drug storage in both branches has almost complied with the newest GMP/CDOB standards. Implementation includes the separation of operational areas, the use of FIFO and FEFO systems, and warehouse temperature control at 25°C and 2-8°C for Cold Chain Products (CCP). However, implementation insufficiency were still found in the handling of Look Alike Sound Alike (LASA) drugs which do not yet use special warning label stickers, as well as shelf cleanliness issues in the Semarang branch due to equipment limitations. PBF Penta Valent has consistently implemented the basic principles of GMP/CDOB Nevertheless, improvements are needed in the visual aspects of LASA and sanitation facilities to maintain optimal drug quality